Monoclonal antibodies: use in rheumatology - Cabello-León, Eduardo (2021)
Advances in the knowledge of the pathophysiological mechanisms of rheumatic diseases have made it possible to identify defined targets to which to direct monoclonal antibodies with therapeutic purposes, a form of treatment commonly called biological therapy. A significant number of these biological drugs are approved by regulatory agencies and are included in the recommendations for the management of various rheumatic diseases; including autoimmune systemic rheumatic diseases; but also spondyloarthritis and other rheumatic diseases. A large number of monoclonal antibodies are in diverse research phases and it is expected that in near future more of these drugs will become available. Used properly they are safe and effective therapies, but they use can be associated with side effects, some of which can be serious. In general they have a high cost and despite the appearance of biosimilar molecules the cost is still high. They are not usually first-line therapy and their use should be rational. This review gives a general scope of most important and approved monoclonal antibodies in the rheumatic diseases.